Turkish and Iranian involvement in Iraq and Syria: Competing strategies, rising threat perceptions, and potentials for conflict - Hamidreza Azizi; Salim Çevik (Stiftung Wissenschaft und Politik (SWP), 2022)
It has become cliché to argue that Turkish-Iranian relations oscillate between a controlled rivalry and limited cooperation. However, in Iraq and Syria, rising tensions between Turkey and Turkey-affiliated groups on the one hand and Iran and Iran-backed groups on the other, have put the two countries on a collision course. Conflictual relations between Turkey and Iran have the potential to destabilise the Middle East and the South Caucasus, spawning additional security risks as well as waves of migration towards Europe. Such a situation could also complicate matters related to European energy security. Europe should remain alert and help to ease tensions through deescalation mechanisms. In this regard, efforts to strengthen Iraqi sovereignty may serve as a preemptive measure.
Keywords: 320; Iraq; Syria; Turkey; Iran; rivalry; cooperation; Middle East; South Caucasus; European energy security; PKK; Kurdish question